Chronic desquamative gingivitis in siblings: A report of two cases - Vijayakar, Harshad N. (Medknow Publications & Media Pvt Ltd, 2014)
Desquamative gingivitis is a gingival response associated with a variety of clinical conditions and characterized by intense erythema, desquamation and ulceration of free and attached gingiva. A variety of diseases such as lichen planus, pemphigus, pemphigoid, dermatitis herpetiformis, linear IgA disease, lupus erythematosus, erythema multiformae manifest clinically as desquamative gingivitis. Of all the disease entities, Lichen Planus is a relatively common disorder affecting the skin and mucous membrane. Very often it has oral manifestations. These lesions of oral lichen planus (OLP) have myriad but distinct morphology. As they mimic other mucocutaneous disorders with regard to clinical appearance, many lesions of oral lichen planus go undiagnosed or are wrongly diagnosed. Reported here are two cases of desquamative gingivitis. One of these was diagnosed as erosive lichen planus based on the symptoms, clinical findings, histologic, and immunofluorescent examination. Further management was done in consultation with a dermatologist.